Immunotherapy of Crohn's disease - C. van Montfrans; L. Camoglio; S. J. H. van Deventer (Mediators of Inflammation)
Although the initiating events of Crohn's disease are unknown, models of experimental colitis have provided new insights in the immunologically mediated pathways of mucosal inflammation. In Crohn's disease activated mucosal T lymphocytes produce proinflammatory cytokines within the mucosal compartment. With this understanding, there has been a shift in past years from the use of unspecific anti-inflammatory agents (corticosteroids, aminosalicylates) to the use of immunomodulatory drugs (azathioprine, methotrexate). Moreover, novel strategies have been designed for specific targets in Crohn's disease, in particular T lymphocytes and cytokines. In an open label study treatment of steroid-refractory Crohn's disease with anti- CD4+ antibodies was well tolerated and showed clinical benefit. However, a sustained depletion of the CD4+ cells precluded further clinical trials. In controlled clinical studies, anti-tumour necrosis factor (TNF-α) antibodies induced com plete remissions and few side effects were observed. One study suggested efficacy in active Crohn's disease of recombinant interleukin-10. Long term treatment studies will have to answer questions about the indications for use, benefit and toxicity. Altogether, these results hold promise for future management of Crohn's disease, where disease-modifying interventions and strategies that effectively maintain disease remission will play a key role.